EFEK EKSTRAK METANOL DAUN SELEDRI (Apium graveolens Linn.) SEBAGAI INSEKTISIDA TERHADAP NYAMUK - Akuba,M.Sc.,Apt, Juliyanty; Thomas, Nurain; Dwy Jayanto Palay, Rendy (Journal Syifa Sciences and Clinical Research, 2019)
The ability of mosquitoes as a vector of various diseases such as dengue and malaria. One of the most commonly used methods of eradicating mosquitoes is chemical insecticides aimed at killing adult mosquitoes, which also creates its own problems, namely the emergence of mosquito resistance and toxic effects on humans. Therefore, alternative insecticides that are safer for the environment are needed from plants. One of them uses celery plants (Apium graveolens Linn.). Celery contains essential oils which act as respiratory poisons that can repel or kill mosquitoes. This study aims to see the effect of methanol extract of celery leaves as insecticides on mosquitoes, carried out by spraying on mosquitoes in confinement. Spraying using water as a negative control, baygon as a positive control and each extract solution 5% b / v, 10% b / v and 15% b / v. Spraying on each cage is done 8 times, ie 2 times from the left side of the cage, 2 times from the right side of the cage, 2 times from the front of the cage and 2 times from the back of the cage. The results showed that testing of methanol extract of celery leaves at a concentration of 5%, 10% and 15% could work as a mosquito-killing insecticide.